KAJIAN TEOLOGI SOSIAL TERHADAP BENCANA ALAM BANJIR BAGI MASYARAKAT KAROMBASAN DI KOTA MANADO TAHUN 2021 - Julio Eleazer Nendissa (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
Flood is one of most dangerous disasters to all living things on earth. Flood natural disaster having occurred Manado city, especially Karombasan village, was caused by heavy rains for days, surface water runoff, low soil infiltration capacity, and littering. Floods that hit Karombasan sub-district have killed 3 persons, and made 1 person missing, 8 houses damaged: 3 heavily damaged and 5 lightly damaged. This paper was organized aiming to know, understand, and analyze the causes of flood in the Karombasan village and what the government's social action is in dealing with the Karombasan community affected by the flood disaster. This paper spotlighted the inventory of flood victims, the causes, how to overcome them, and social actions taken by the government to overcome the floods occurring. A qualitative research method with a descriptive approach was used in this study and data collection techniques used was in-depth interviews. The results show natural factors of heavy rain, human factors such as littering, and illegal logging causing the flood natural disaster. As a result of flood, casualties, missing victims, injuries, lost valuable documents, lost and damaged properties, damaged houses and economic disruption can be found in local community.